Making the Indian Church More Synodal - John Crasta (Asian Horizons, 2025)
In view of the synodal movement, we need to acknowledge that the responsibility of transforming the Indian Church into a synodal Church is the task of every Catholic faithful. We have to encounter Jesus together. In the light of the synod’s purpose and focus, this article explores possibilities of making the Indian Church more synodal than it is today. The synodal process seeks to facilitate the people of God to experience journeying together, to think and reflect together, and to discern and decide together. The ongoing synodal journey necessitates the entire people of God, leaving out none, to acknowledge their specific vocation in the Church and work towards the realisation of this vocation. Hence, for the Indian Church to be more synodal means to be more democratic, and to be more democratic necessarily entails to be more participatory and consultative in decision-making and implementation. Accordingly, this paper explores into different means and methods of making the Indian Church more synodal.